2017
DOI: 10.1016/j.jnucmat.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation effects in beryllium exposed to high energy protons of the NuMI neutrino source

Abstract: has been irradiated by 120GeV protons over 7 years, with a maximum integrated fluence at the window centre of 2.06 10 22 p/cm 2 corresponding to a radiation damage level of 0.48 dpa. The proton beam is pulsed at 0.5 Hz leading to an instantaneous temperature rise of 40°C per pulse. The window is cooled by natural convection and is estimated to operate at an average of around 50°C. The microstructure of this irradiated material was investigated by SEM / EBSD and Atom Probe Tomography, and compared to that of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…*Measured before irradiation. www.nature.com/scientificreports www.nature.com/scientificreports/ previous publications 19,34 suggest that these complex structures are beryllium intermetallic compounds. The post irradiation examination of HIDOBE1 campaign also confirmed the presence of complex beryllide particles with Fe/Al/Mn or Fe/Al/Mn/Cr composition 35 .…”
Section: Second Phase Precipitates and Segregation After Irradiationmentioning
confidence: 99%
“…*Measured before irradiation. www.nature.com/scientificreports www.nature.com/scientificreports/ previous publications 19,34 suggest that these complex structures are beryllium intermetallic compounds. The post irradiation examination of HIDOBE1 campaign also confirmed the presence of complex beryllide particles with Fe/Al/Mn or Fe/Al/Mn/Cr composition 35 .…”
Section: Second Phase Precipitates and Segregation After Irradiationmentioning
confidence: 99%
“…Another essential factor to consider when determining safety margins for beam-intercepting devices is the long-term radiation damage effects on material properties. Previous studies [13,21,22] have shown a significant degradation in thermal and strength properties of beryllium from high energy particle irradiation, which can have a negative impact on the structural and thermal integrity of the component over time. Therefore, careful consideration of radiation damage effects and the resulting material property degradation is needed when evaluating the thermomechanical response of beam-intercepting devices.…”
Section: Discussionmentioning
confidence: 99%
“…An irradiated disc of PF-60 grade beryllium was recovered from the Fermilab NuMI primary beam window assembly and sent to the University of Oxford for PIE activities [13]. The beryllium disc was exposed to a total of 1.6 × 10 21 protons (120 GeV), equivalent to about 0.5 peak DPA, with an irradiation temperature of about 50 °C.…”
Section: Numi Beryllium Window Analysismentioning
confidence: 99%